2018
DOI: 10.1002/aenm.201802836
|View full text |Cite
|
Sign up to set email alerts
|

Higher Mobility and Carrier Lifetimes in Solution‐Processable Small‐Molecule Ternary Solar Cells with 11% Efficiency

Abstract: shown to reach power conversion efficiencies (PCEs) >10%, [2] the synthesis of π-conjugated polymers with specific optical gaps and little-to-no batch-to-batch variation remains a practical limitation in the scaling-up of high-efficiency polymerfullerene BHJ devices. [3] In parallel, the narrow spectral absorption of fullerene acceptors (e.g., [6,6]-phenyl-C 61 (or C 71 )butyric acid methyl ester, namely, PC 61 BM and PC 71 BM) falling in the short-wavelengths region (≈300-450 nm) inherently limits photonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 69 publications
3
54
0
Order By: Relevance
“…Here, PB D rises due to hole transfer from ICC6 to DR3. We note that charge generation is slower than in the binary DR3:ICC6 blend due to larger ICC6 domains, as indicated by scanning tunneling electron microscopy (STEM) imaging coupled with electron energy‐loss spectroscopy (EELS) reported earlier by Liang et al This is also in line with the increased PL lifetime seen in ternary blends compared to binary blends (see Table ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Here, PB D rises due to hole transfer from ICC6 to DR3. We note that charge generation is slower than in the binary DR3:ICC6 blend due to larger ICC6 domains, as indicated by scanning tunneling electron microscopy (STEM) imaging coupled with electron energy‐loss spectroscopy (EELS) reported earlier by Liang et al This is also in line with the increased PL lifetime seen in ternary blends compared to binary blends (see Table ).…”
Section: Resultssupporting
confidence: 85%
“…The addition of PC 71 BM not only enhances the EQE in the 350–450 nm region, but surprisingly also improves the EQE across the entire absorption range of the ternary blend. This improvement is a consequence of the improved charge carrier mobility in ICC6 due to increased crystallinity of ICC6 upon blending with PC 71 BM, as has recently been demonstrated by Liang et al However, excess of PC 71 BM deteriorates the EQE due to morphological changes and decreased crystallinity . In line with the higher EQE, the internal quantum efficiency (IQE) increases, reaching >90% for the fully optimized ternary devices.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The ternary blend of SBDT‐BDD: IDIC :PC 71 BM exhibited an enhanced PCE of 10.9% due to increased photoabsorption, and optimal morphology led to higher J SC and FF. Beaujuge et al also reported an ASM‐ternary OSC using a blend of DR3TBDTT: IDIC :PC 71 BM exhibiting a high PCE of 10.8% due to low recombination losses …”
Section: Other Aspects Of Frea Oscsmentioning
confidence: 98%
“…Recently, combining the advantages of nonfullerene acceptors, ternary solar cells using two NFAs (1D/2NFA) yield over 16% efficiency . However, the active layers of most high‐performance ternary solar cells need extra post‐treatments or solvent additives, which may limit their future applications . Hence, developing ternary solar cells without the need of using these extra treatments is highly desired.…”
Section: Introductionmentioning
confidence: 99%